Experimental and computational study on the influence of geometric characteristics of mineral filler on mastic rheological behavior. (March 2023) - Xing, Baodong; Lv, Xiaobo; Song, Aiming; Fang, Chen; Fan, Weiyu; Lyu, Yuchao
Abstract: The article aims to appraise the relationship between filler geometry and mastic rheological behavior. Limestone and granite filler with four size fractions were produced and optimized via simplex centroid design. Their geometrical characteristics were characterized by grading tests and digital imaging processes. The rheological properties of mastics were evaluated using a dynamic shear rheometer. Results revealed that each granite filler had more regular contour shape (except g1 ), richer angularity (except g1, g2, g5 and g17 ) and surface texture than corresponding limestone filler. The established dynamic viscoelastic model based on fractional theory was found to agree well with experimental data, indicating mastic rheological behavior could be accurately modeled. Furthermore, grey relational analysis results demonstrated that particle shape and angularity were the determining influential factors for mastic rheological behavior, regardless of filler types. All the results were instructive to select the appropriate fillers that produced mastics with desired performance. Graphical Abstract: ga1 Highlights: Composite morphological features of filler are well characterized. Simplex centroid design was used to optimize four-component blends. The established dynamic viscoelastic model can effectively appraise mastic rheological behavior. Rheology response is related to geometrical characteristics of filler.